Efficacy of Balance and Eye-Movement Exercises for Persons With Multiple Sclerosis (BEEMS). (27th February 2018) - Hebert, Jeffrey R.; Corboy, John R.; Vollmer, Timothy; Forster, Jeri E.; Schenkman, Margaret
Abstract : Objective: To determine whether a multifaceted vestibular-related rehabilitation program (Balance and Eye-Movement Exercises for Persons with Multiple Sclerosis; BEEMS) improves balance in persons with MS and whether there are differences in outcomes based on brainstem/cerebellar lesion involvement. Methods: A 2-arm, examiner-blinded, stratified (involvement vs no involvement of brainstem/cerebellar structures), randomized controlled trial was implemented. Eighty-eight participants were allocated to BEEMS or no treatment control. Computerized Dynamic Posturography-Sensory Organization Test (CDP-SOT) measured balance control. The Dizziness Handicap Inventory (DHI), Modified Fatigue Impact Scale (MFIS), and Short Form-36 Health Status Questionnaire (SF-36) were also administered. Linear mixed models were used to investigate the primary and secondary aims. Results: From baseline to 6 weeks, BEEMS participants experienced greater improvements compared to control participants in CDP-SOT composite (model-estimated difference in change 4.9, 95% confidence interval 1.39–8.38, p = 0.006), DHI total (−13.5, −17.7 to −7.25, p < 0.0001), MFIS total (−11.4, −15.7 to −7.0, p < 0.0001), SF-36 Mental (5.6, 2.43–8.71, p = 0.0006), and SF-36 Physical (3.5, 1.12–5.81, p = 0.004) scores and from baseline to 14 weeks in CDP-SOT composite (8.3, 4.73–11.9, p < 0.0001), DHI total (−13.9, −19.3 to −8.62, p < 0.0001), MFIS total (−12.3, −16.7 to −7.79, p < 0.0001), SF-36 Mental (3.9, 0.70–7.16, p = 0.02), and SF-36 Physical (3.2, 0.79–5.62, p = 0.01) scores. From baseline to 6 weeks, BEEMS participants with brainstem/cerebellar lesion involvement experienced greater improvements compared to those without in CDP-SOT composite (5.26, 0.34–10.2, p = 0.04) and MFIS total (−7.6, −14.0 to −1.33, p = 0.02) scores. Conclusion: BEEMS improved multiple outcomes regardless of whether brainstem/cerebellar lesions were present, supporting the generalizability of BEEMS for ambulatory people with MS who have at least minimally impaired balance and fatigue. Clinical trials.gov identifier: NCT01698086. Classification of evidence: This study provides Class I evidence that BEEMS training improves dynamic posturography-based balance, dizziness, fatigue, and quality of life in persons with MS.